Hypoxia-Inducible Factor 1A Upregulates HMGN5 by Increasing the Expression of GATA1 and Plays a Role in Osteosarcoma Metastasis. (16th December 2019) - Xu, Enjie; Ji, Zhe; Jiang, Heng; Lin, Tao; Ma, Jun; Zhou, Xuhui
Abstract : Osteosarcoma is one of the most common malignant tumors in children and adolescents and is characterized by early metastasis. High-mobility group N (HMGN) domains are involved in the development of several tumors. Our previous study found that HMGN5 is highly expressed in osteosarcoma tissues and knockdown of HMGN5 inhibits migration and invasion of U-2 OS and Saos-2 cells. A hypoxic environment is commonly found in solid tumors such as osteosarcoma and is likely to be associated with tumor metastasis, so we further explored the relationship between HMGN5 and the hypoxic environment. Hypoxia-inducible factor 1A (HIF1A) is an adaptive factor in the hypoxic environment. We found that HIF1A and HMGN5 were upregulated in osteosarcoma (OS) cells cultured in the hypoxic environment, and the results of overexpression and knockdown experiments showed that HIF1A upregulated the transcription factor GATA1 and further promoted the expression of HMGN5. In addition, MMP2 and MMP9 were subsequently upregulated through the c-jun pathway, and finally, this promoted the migration and invasion of OS cells. It is suggested that HMGN5 may be an important downstream factor for HIF1A to promote osteosarcoma metastasis. It has an important clinical significance for the selection of therapeutic targets for osteosarcoma.